KOMODIFIKASI BUDAYA LOKAL DALAM MEDIA PROMOSI KESEHATAN - Dewi, Alit Kumala (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2024)
When associated with commodification, advertising significantly impacts everything by turning it into a commodity-oriented to profit or having economic value. Cultural commodification is a change in part or almost all parts of culture to make it more commercial and have a high selling value, with the main aim of attracting the public's interest as consumers. This research aims to understand and comprehensively describe the commodification of local culture in health promotion media. The object of study is local Balinese cultural wisdom, especially in the health sector. This research uses qualitative methods which can be interpreted as researchers describing research results descriptively, using observation data collection methods, literature studies, interviews, and online data search methods. The research results show that local Balinese cultural wisdom, including Balinese traditional medicine, Balinese spiritual traditions, and Balinese traditional medicinal products, has been identified as having been commodified. This can be known as changes or shifts in form, function, and meaning. At first, it was humanitarian-oriented, and there was a shift towards being profitable, although it cannot be generalized, some sacred traditions slowly became profane, and exclusive knowledge and skills that have local wisdom value can be possessed and learned through promotional courses and training